Isoquinoline alkaloids from Hylomecon japonica and their potential anti-breast cancer activities. (October 2022) - Cao, Zhen; Zhu, Shangjun; Xue, Zhaowei; Zhang, Fuxin; Zhang, Lei; Zhang, Yu; Guo, Yuting; Zhan, Guanqun; Zhang, Xinxin; Guo, Zengjun
Abstract: Four pairs of undescribed enantiomeric isoquinoline alkaloids (6S/R-(N, N-diethylacetamido)yl-dihydrochelerythrine, 6R/S-acetonyl-9-hydroxy-dihydrochelerythrine, 6S/R-acroleinyl-dihydrochelerythrine, 6S/R-acetatemethyl-dihydrochelerythrine), five undescribed isoquinoline alkaloids (6, 10-dimethoxydihydrochelerythrine, 6-ethoxy-ethaniminyl-dihydrochelandine, 9-hydroxy-dihydrochelerythrine, 9-methoxy-10-hydroxy-norchelerythrine, chelidoniumine A), together with 13 known isoquinoline alkaloids were isolated from an extract of the roots and rhizomes of Hylomecon japonica . The structures of the undescribed compounds were identified by NMR, HRESIMS, UV, IR, and their absolute configurations were defined via electronic circular dichroism data and optical rotation. All of the isolated compounds were tested for their anti-breast cancer activities in MCF-7 cells. Among them, the undescribed alkaloids 6S/R-acroleinyl-dihydrochelerythrine, 6, 10-dimethoxydihydrochelerythrine, 6-ethoxy-ethaniminyl-dihydrochelandine, 9-methoxy-10-hydroxy-norchelerythrine and other known alkaloids 6-methoxydihydrosanguinarine, 6-acetaldehyde-dihyrochelerythrine, dihydrosanguinaline and 10-methoxy boconoline had good inhibitory effects on MCF-7 cells of breast cancer with an IC50 lower than 20 μM. Graphical abstract: 13 undescribed isoquinoline alkaloids together with 13 known isoquinoline alkaloids were obtained from the roots and rhizomes of Hylomecon japonica, and some of the isolated compounds had good inhibitory effects on MCF-7 cells of breast cancer with an IC50 lower than 20 μ. Image 1 Highlights: 26 isoquinoline alkaloids were obtained, including 13 undescribed and 13 known. Further enriched the understanding of isoquinoline alkaloids in Hylomecon japonica . The separation of racemes was realized by various separation methods. The anti-breast cancer activities of 26 isoquinolines were determined by MTT assay. Provided a basis for understanding the anti-tumor activity of Hylomecon japonica .